Proterozoic mantle melting recorded by the Re-Os isotopic systematics of ophiolites from the Qilian Orogenic Belt, northwestern China. (January 2023) - Zhao, Jing; Xiao, Qianru; Gao, Yilin; Zuo, Rui; Huang, Luyu; Li, Jie; Long, Xiaoping
Graphical abstract: Highlights: The Minhe serpentinites are mantle residues of multi-episode partial melting. Fluid/melt metasomatism exerted a limited impact on the Re-Os systematics. Re-Os ages provide temporal constraints on Proterozoic melt extraction. Abstract: Re-Os isotopes of the mantle-derived ultramafic rocks can provide temporal constraints on the melt extraction of ancient mantle. Here, new geochemistry and Re-Os isotopes of serpentinites from the Minhe ophiolite in the Qilian Orogenic Belt (QOB) are presented. Their geochemical compositions (e.g., abundances of heavy rare earth elements, Al2 O3, Yb, Re, and Th/Yb ratio) suggest that protoliths of the serpentinites originated as mantle residues. They underwent multiple episodes of melt depletion, leading to a highly refractory nature and high degrees of partial melting (>18%). Moreover, subchondritic 187 Re/ 188 Os (0.0023–0.0399) and 187 Os/ 188 Os (0.1135–0.1210) ratios of the serpentinites, and decoupling of the Re-Os systematics and metasomatic proxies (e.g., LOI, Sr, La, and Th/Yb), demonstrate that fluid/melt metasomatism exerted a limited impact on their Re-Os isotopic systematics. Their Re-depletion ages (TRD ), varying from 1.22 to 2.21 Ga, are analogues to their Re-Os model ages (TMA, 1.29–2.31 Ga). Therefore, Re-Os isotopic ages recorded by ophiolites in QOB indicate that at least two major melt-extraction episodes occurred in the lithospheric mantle during Proterozoic (1.2–1.6 Ga and 2.0–2.2 Ga). Notably, the 1.2–1.6 Ga mantle melt-depletion event may have a genetic affinity with the 1.1–1.7 Ga crustal growth. Mantle rocks from an ophiolite have a great potential in tracking ancient geological events, such as Precambrian mantle melting.